Study on Genetic Polymorphism in Genes Related to Prolificacy and Foetal Growth using PCR-RFLP in Surti Goats - Dangar, Nikhil S.; Pandya, Gaurav M.; Ramani, Umed V.; Patel, Santul S.; Ansari, Farheen (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The Surti is a dual-purpose goat breed of Gujarat. The Insulin-like Growth Factors Binding Protein 3 (IGFBP3), POU Class 1 Homeobox 1 (POU1F1), G-protein coupled Receptor 54 (GPR54), and Fecundity Gene Boorla (FecB) are playing a role in ovulation, prolificacy, and fetal growth. Mutation in Exon-2 Partial Intron-2 with the base size 316 bp, Exon-4 with the base size 508 bp, Exon-5 with the base size 250 bp, and Exon-6 with base size 190 bp region of IGFBP3, POU1F1, GPR54, and FecB genes, respectively, is reported to be related with increased prolificacy and fetal growth. Based on the known mutation information in goat and sheep, PCR primers were designed to screen polymorphism in a total of 50 Surti goats. During the PCR-RFLP study, no polymorphic sites were found for the region abovementioned IGFBP3, POU1F1, GPR54, and FecB genes in Surti goats.